Decline in agricultural activity around Lake Chad: Any prospect for restoration? A Review - Alhassan, A. B.; Chiroma, A. M.; Kundiri, A. M.; Bababe, B.; Tekwa, I. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Lake Chad that has been an economic hub for centuries has in the last few decades witnessed continued degradation threatening food security and livelihood of the population who depend on the lake for a living. The impact of depletion of the lake is being felt by an estimated 30 million people from the four riparian states, namely: Cameroon, Chad, Niger and Nigeria. This paper focuses on the causes of low agricultural activity around Lake Chad with particular emphasis on crop production. The paper also highlights the prospects for reviving agricultural activity through implementation of innovative soil management techniques. Analysis of the literature revealed that in addition to devastating effects of violent armed conflict on livelihood conditions in this region, frequent drought, dwindling rainfalls, degraded soils and sparser vegetation cover are among the factors responsible for the low agricultural activity in this region where a large proportion of the population relies on rainfed agriculture. The review revealed that organic farming practices that support biodiversity has the potential for besides improving soil health and reduce pest pressure, also improve crop yields and protect the environment. Furthermore, the use of biofertilizers to reduce the dependence on conventional inorganic fertilizers by farmers offers the means of mitigating the declining soil mineral nutrient reserves in this region. It is envisaged that restoring the lake to its near original state coupled with improving the productivity of the fragile soils will go a long way in addressing the challenges of food insecurity, a major factor stabilizing factor in the area.